Análisis antropométrico para la normalización del tallaje de la población peruana - Salazar Medina, Nicolás (2015)
nsalazar@ulima.edu.pe; rlariosf@ulima.edu.pe; mhenrich@ulima.edu.pe; arvera@ulima.edu.pe; grschofield@yahoo.es